Meningkatkan Loyalitas Pengguna Mobile Banking Bank BPD DIY melalui Layanan, Kepercayaan, dan Kemudahan Penggunaan - Irawati, Yuyun Febrian; Ginting, Ginta; Priansa, Donni Juni (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The Indonesian banking industry continues to grow with the introduction of m-banking technology. As a regional bank, Bank BPD DIY must maintain customer loyalty amidst competition with national banks. This study aims to analyze the effect of service quality, trust, and ease of use on the satisfaction and loyalty of BPD DIY mobile banking application users. This study uses a quantitative method with a structural equation modeling (SEM) approach involving 383 respondents of BPD DIY m-banking users and analyzed with PLS software. Measurements use a Likert scale. The results of the study indicate that service quality, trust, and ease of use have a significant effect on satisfaction and loyalty. Satisfaction also mediates between independent variables and loyalty. The implication of this study is that regional banks, especially BPD DIY, must further improve the quality of their digital services and build customer trust through ease of use to maintain customer loyalty in the digital era.